Energy-consumption monitoring towards decarbonisation : insights from the Basque albacore artisanal fisheries - Gabiña, Gorka; Caballero, Ainhoa; Goikoetxea, Nerea; Castresana, Joseba; Goñi, Nicolas; Sagarminaga, Yolanda; Basurko, Oihane C. (Frontiers Media S.A., 2025)
This study presents a low-cost monitoring approach to assess energy consumption and carbon footprint in the Basque artisanal albacore fishery, focusing on two fishing techniques: trolling (LTL) and pole-and-line with live bait (LHP). Using intrusive and non-intrusive monitoring systems, vessel-specific fuel consumption–speed over ground curves (FOC-SOG) were established, enabling accurate estimation of fuel use and greenhouse gas (GHG) emissions across five fishing seasons (2015–2019). The results show that LTL vessels, although having bigger engines, exhibit higher fuel use intensity (FUI: 899.2 L/t) and carbon intensity (2.45 kg CO2eq/kg landed) compared to LHP vessels (FUI: 632.6 L/t; 1.72 kg CO2eq/kg landed), due to lower catch volumes and longer distance covered. Despite their higher fuel consumption, LHP vessels achieve greater catches, making them relatively more energy efficient. The study also confirms that vessel speed is a key factor in fuel consumption, validating the use of SOG as a proxy for energy demand. This research demonstrates the feasibility of applying low-cost monitoring strategies to small-scale fisheries, offering a scalable method for evaluating operational patterns and supporting decarbonisation efforts. The findings provide a solid foundation for future energy-saving measures tailored to each fishing technique, contributing to the broader goal of reducing the environmental impact of artisanal fleets.
Keywords: energy monitoring; fisheries decarbonisation; fuel use intensity; carbon footprint; Bay of Biscay